THE EFFECT OF STARFRUIT (Averrhoa bilimbi L.)JUICE ON THE BLOOD TOTAL CHOLESTEROL LEVEL OF WISTAR RATS (Rattus norvegicus) FED WITH HIGH-FAT DIET - Putri Diana Mauliyah Ulfa; IGM. Antara Hambarsika; Indri Ngesti Rahayu (Universitas Hang Tuah, 2019)
ABSTRACT Background: Hypercholesterolemia is a condition in which increased cholesterol concentration in the blood exceeds normal values. Consuming fats and foods rich in cholesterol can increase total cholesterol levels in the blood and cause cholesterol buildup in the arteries. Starfruit (Averrhoa bilimbi L.) has saponin and flavonoid compounds which are expected to play a role in reducing total cholesterol levels. The aim of this study is to determine the effect of star fruit juice (Averrhoa bilimbi L.) to total cholesterol blood levels of male Wistar strain (Rattus norvegicus) with a high-fat diet. Method: Experimental study with post-test only control group design. Twenty-four male white rats (Rattus norvegicus) of the Wistar strain are divided into 3 groups: the experimental group which is given standard diet for 28 days; group of experimental animals who were given a high-fat diet for 28 days; the experimental group treated with a high-fat diet for 28 days and on the 15th until 28th days were given starfruit juice (Averrhoa bilimbi L.) with a dose of 4ml/200grwieght/day. On the 29th day, it is measuredtotal cholesterol levels for all groups of experimental animals. Results: The One-Way ANOVA test shows a significant increase in the average of total cholesterol levels (p = 0,009) in group of experimental animals that are given a high-fat diet (x = 60,625± 3,462mg/dL) compared to groups of experimental animals given standard diet (x = 50± 8,468mg/dL). There is a increase in the average in cholesterol level of the experimental group given a high-fat diet and the starfruit juice (Averrhoa bilimbi L.) (x = 65,5 ± 8,960) compared to the mean total cholesterol level of group of animals given a high-fat diet (x = 60,625± 3,462). However, there is no significant increase (p = 0,201). Conclusion: Administration of starfruit juice (Averrhoa bilimbi L.) was not significantly difference in statistics on average of cholesterol level to male wistar rat (Rattus norvegicus) induced by high fat diet